Distinct Activities of Exonuclease 1 and Flap Endonuclease 1 at Telomeric G4 DNA - Vallur, Aarthy C. (Public Library of Science, 2010)
BACKGROUND: Exonuclease 1 (EXO1) and Flap endonuclease 1 (FEN1) are members of the RAD2 family of structure-specific nucleases. Genetic analysis has identified roles for EXO1 and FEN1 in replication, recombination, DNA repair and maintenance of telomeres. Telomeres are composed of G-rich repeats that readily form G4 DNA. We recently showed that human EXO1 and FEN1 exhibit distinct activities on G4 DNA substrates representative of intermediates in immunoglobulin class switch recombination. METHODOLOGY/PRINCIPAL FINDINGS: We have now compared activities of these enzymes on telomeric substrates bearing G4 DNA, identifying non-overlapping functions that provide mechanistic insight into the distinct telomeric phenotypes caused by their deficiencies. We show that hFEN1 but not hEXO1 cleaves substrates bearing telomeric G4 DNA 5′-flaps, consistent with the requirement for FEN1 in telomeric lagging strand replication. Both hEXO1 and hFEN1 are active on substrates bearing telomeric G4 DNA tails, resembling uncapped telomeres. Notably, hEXO1 but not hFEN1 is active on transcribed telomeric G-loops. CONCLUSION/SIGNIFICANCE: Our results suggest that EXO1 may act at transcription-induced telomeric structures to promote telomere recombination while FEN1 has a dominant role in lagging strand replication at telomeres. Both enzymes can create ssDNA at uncapped telomere ends thereby contributing to recombination.